Adsorptive mutation and N-linked glycosylation modulate influenza virus antigenicity and fitness - Joshua E. Sealy; Thomas P. Peacock; Jean-Remy Sadeyen; Pengxiang Chang; Holly J. Everest; Sushant Bhat; Munir Iqbal (Emerging Microbes and Infections)
Influenza viruses have an error-prone polymerase complex that facilitates a mutagenic environment. Antigenic mutants swiftly arise from this environment with the capacity to persist in both humans and economically important livestock even in the face of vaccination. Furthermore, influenza viruses can adjust the antigenicity of the haemagglutinin (HA) protein, the primary influenza immunogen, using one of four molecular mechanisms. Two prominent mechanisms are: (1) enhancing binding avidity of HA toward cellular receptors to outcompete antibody binding and (2) amino acid substitutions that introduce an N-linked glycan on HA that sterically block antibody binding. In this study we investigate the impact that adsorptive mutation and N-linked glycosylation have on receptor-binding, viral fitness, and antigenicity. We utilize the H9N2 A/chicken/Pakistan/SKP-827/16 virus which naturally contains HA residue T180 that we have previously shown to be an adsorptive mutant relative to virus with T180A. We find that the addition of N-linked glycans can be beneficial or deleterious to virus replication depending on the background receptor binding avidity. We also find that in some cases, an N-linked glycan can trump the effect of an avidity enhancing substitution with respect to antigenicity. Taken together these data shed light on a potential route to the generation of a virus which is “fit” and able to overcome vaccine pressure.